Heuristic political behavior in the 2024 presidential general election: Fandom humanies case study - Husna, Dwi (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2024)
The K-Popers phenomenon in the elections in Indonesia in 2024 is the first record in the history of election contestation because it contains a combination of South Korean Pop culture and Indonesian Politics. K-Pop fans have the characteristics of a strong social group so that when they enter politics they join the Humanies fandom and form a social group that supports Anies Baswedan as a candidate for President of Indonesia in 2024-2029. This research aims to describe the representation of heuristic political behavior from the Humanies fandom in the 2024 elections. This research uses qualitative research methods with a literature study approach. So the data source in this research comes from secondary data. The research results show that the representation of heuristic political behavior from the Humanies fandom is in the form of creating a social media account K-Pop terms in updates on Anies' activities, right up to making fan merch (photocards, light sticks, glasses, etc.). The political behavior carried out by individuals in the Humanies fandom is based on the styles of K-Popers present in politics which have inadvertently been formed by Anies. This K-Popers style ultimately makes individuals in the Humanies fandom more expressive in politics.